Anisotropy-based mechanism for zigzag striped patterns in magnetic thin films - Billoni, Orlando Vito (2014)
In this work, we studied a two-dimensional ferromagnetic system using Monte Carlo simulations. Our modelincludes exchange and dipolar interactions, a cubic anisotropy term, and uniaxial out-of-plane and in-planeones. According to the set of parameters chosen, the model including uniaxial out-of-plane anisotropy has aground state which consists of a canted state with stripes of opposite out-of-plane magnetization. When the cubicanisotropy is introduced, zigzag patterns appear in the stripes at fields close to the remanence. An analysis of theanisotropy terms of the model shows that this configuration is related to specific values of the ratio between thecubic and the effective uniaxial anisotropy. The mechanism behind this effect is related to particular features ofthe anisotropy’s energy landscape since a global minima transition as a function of the applied field is required inthe anisotropy terms. This mechanism for zigzag formation could be present in monocrystal ferromagnetic thinfilms in a given range of thicknesses.